2018
DOI: 10.1093/jhps/hny021
|View full text |Cite
|
Sign up to set email alerts
|

The role of cell therapies and hip arthroscopy in the management of osteonecrosis: an update

Abstract: The exact pathophysiology of osteonecrosis of the femoral head (ONFH) is still unknown. There is evidence to suggest that in ON there is decreased population and altered function of the mesenchymal stem cells (MSCs) of the femoral head. This could influence both the actual occurrence of ON itself and the repair process that follows. Hence, in such an environment it only is rational to consider the use of cell-based treatments to potentially regenerate lost or damaged bone. The aim of this review is to provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 59 publications
0
5
0
1
Order By: Relevance
“…The addition of fibula and vascularized grafts to CD have shown promising results but are challenging surgeries to perform and have donor site co-morbidities. On the other hand, newer orthobiologics have been increasingly tested in the past decade; bone marrow aspirate concentrate (BMAC), platelet-rich plasma (PRP) and bone morphogenetic protein-7 (BMP-7) have been supplemented with CD to increase the success rates in early AVN [ 14 17 ]. A few studies have even assessed these in post-femoral head collapse and distortion stages [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The addition of fibula and vascularized grafts to CD have shown promising results but are challenging surgeries to perform and have donor site co-morbidities. On the other hand, newer orthobiologics have been increasingly tested in the past decade; bone marrow aspirate concentrate (BMAC), platelet-rich plasma (PRP) and bone morphogenetic protein-7 (BMP-7) have been supplemented with CD to increase the success rates in early AVN [ 14 17 ]. A few studies have even assessed these in post-femoral head collapse and distortion stages [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mono-nuclear stem cells, which are building blocks of hip's skeletal anatomy, are found in bone marrow aspiration concentrate (BMAC). They develop into bone-forming cells replacing old, faulty cells, preserving structural balance & integrity [16][17][18][19]. Introducing fresh pool of lineage cells capable of differentiating into cells required for hip's normal physiology appears to be promising therapy option for pre collapse phases of AVN.…”
Section: Core Decompression + Bmacmentioning
confidence: 99%
“…Fibular & vascular grafts have been added with CD with better results, however they're difficult operations to execute. Newer orthobiologics, are progressively investigated in last 10-12 years; CD has been augmented with BMAC, PRP, & BMP-7 to boost the success rates [14][15][16][17]. Less studies [18,19] had looked at them in the later stages.…”
Section: Introductionmentioning
confidence: 99%
“…The results are inconclusive due to the vast difference in the time period for the two trials and further RCTs are needed. In 2016, the systematic review by Papakostidis et al 45 found the likelihood of the femoral head advancing to the collapse stage were decreased when compared to the CD group (OR=0.2; 95%CI:= 0.08 to 0.6; p=0.02). However, this systematic review included three retrospective case-control trials [46][47][48] , along with one prospective pilot trial 49 , which were all excluded from our systematic review due to our inclusion/exclusion criteria of including only prospective RCTs.…”
Section: Collapse Of the Femoral Headmentioning
confidence: 99%